2010
DOI: 10.1017/s0029665110003010
|View full text |Cite
|
Sign up to set email alerts
|

Selenium intakes in UK South Asian and Caucasian women: a longitudinal analysis

Abstract: Selenium (Se) is a trace mineral and component of selenoproteins known to be crucial for immune and thyroid function and reproduction (1) . Better Se status has also been linked to lower mortality, slower cognitive decline, reduced viral virulence and lower cancer risk (1) . Se status in the UK is believed to be low (1) . This study used data collected in the D-FINES (Vitamin D, Food Intake, Nutrition and Exposure to Sunlight in Southern England) study to investigate the Se intake of UK women by ethnicity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…The number of women that had Se intakes below the LRNI or RNI was not significantly different in terms of ethnicity. Only in the South Asian women was a seasonal variation noted, with significantly lower Se intake in the autumn [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of women that had Se intakes below the LRNI or RNI was not significantly different in terms of ethnicity. Only in the South Asian women was a seasonal variation noted, with significantly lower Se intake in the autumn [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…UK studies, including a broad range of population groups, identified a fairly consistent overall suboptimal Se status in this country based on the range of 90–100 μg/L to achieve maximum GPx expression [ 20 , 37 , 60 , 70 , 71 , 77 , 78 , 79 , 80 , 81 ]. Pre-term infants in the Hampshire area who had received parenteral nutrition and blood transfusions had significantly lower mean plasma Se levels that normalised by six months of gestation-corrected age.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low nutrient densities of retinol, vitamin D, magnesium, potassium, copper, selenium, and monounsaturated fatty acids were significantly lower than the recommendations. The few studies and national surveys assessing micronutrient intakes have also found low nutrient intakes of retinol, vitamin D and selenium, particularly in women from South Asian origin (Nelson et al 2007;Darling et al 2010;Mavroeidi et al 2010). Low levels of mono-unsaturated fats have also been reported among South Asians living in the UK (Garduno-Diaz and Khokhar 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The study also investigated selenium intakes of South Asian ( n = 55) and Caucasian women ( n = 248). South Asian women were found to consume less selenium compared with Caucasian women, while intakes for both groups were found to be below the LRNI (Darling et al . 2010), which is of concern as an adequate intake is important for immune and thyroid functions and reproduction (British Nutrition Foundation 2001).…”
Section: Overview Of the Health Profile And Dietary Habits Of Minormentioning
confidence: 99%